Cyber Security Risk Management in Critical Infrastructure and Public Services - Anteng Nirwanto; Najwa Filza; Kafka Anwijzi; Rona Kartika Cahya Wulan (Proceeding International Conference Restructuring and Transforming Law, 2026)
The development of information and communication technology has driven digital transformation in various sectors, particularly critical infrastructure and public services. However, increased connectivity and dependence on digital systems have also been accompanied by increasingly complex cybersecurity threats. This study aims to analyze cybersecurity risk management in critical infrastructure and public services through the stages of risk identification, evaluation, and mitigation. The method used is a systematic literature review by reviewing various academic sources, technical reports, and policy documents related to cybersecurity. The results show that cyber threats such as malware, phishing, DDoS attacks, data leaks, and insider threats are the main risks faced by organizations. Risk evaluation is carried out by considering the level of likelihood and impact, thus determining appropriate handling priorities. Effective mitigation strategies include the implementation of security technologies such as firewalls, IDS/IPS, data encryption, the Zero Trust Architecture approach, increasing human resource capacity, and strengthening security policies and governance. Furthermore, the use of artificial intelligence and machine learning technologies provides innovative solutions for detecting threats in real time. Thus, the implementation of comprehensive and sustainable cybersecurity risk management is essential to improve system resilience and maintain the continuity of public services amidst the ever-evolving dynamics of cyber threats.